Pelatihan Pemanfaatan Media Digital sebagai Sarana Belajar bagi Santri Pondok Pesantren Minharuj Rufaq’ - Ridwan Ridwan; Erni Mariana; Sulis Anjarwati; Nurkaif Nurkaif; Ayang Kinasih (Pakis Journal Institute, 2026)
This community service activity was held to help improve students' digital literacy and skills in using technology and digital media. The goal is to enable them to utilize these tools to learn effectively, innovatively, and responsibly. This program is aimed at students in Islamic boarding schools who still experience difficulties in using digital technology to support their learning process. This activity was implemented through several steps, namely socialization, training, hands-on practice, and mentoring. The material presented included an introduction to various types of digital media used in education, how to use applications for online learning, the use of educational videos, techniques for finding reliable learning resources, and an understanding of ethics and security when using digital media. The activity was conducted interactively through demonstrations, discussions, and practice using existing digital tools. The results showed an increase in students' knowledge and skills in using digital media as a learning resource. In addition, students became more motivated to study independently, were able to access various online learning materials, and had a better understanding of using digital media wisely and productively. The enthusiasm of the participants was evident in their ability to integrate digital technology into religious and general education lessons. Overall, this community service activity has had a positive impact on improving the quality of student learning in the digital era. It is hoped that training programs like this can be implemented continuously in the future as a first step toward developing a technology-based learning system in Islamic boarding schools.